The developing human : clinically oriented embryology - Moore, Keith L. 4 0 16; Persaud, T. V. N.; 5 (Philadelphia : Saunders, 2003)
Chronicles the development of the human embryo's organs and systems week by week, and explains when and why specific birth defects occur.
Includes bibliographical references and index.
Young Adult;Young Adult.
Keywords: 2 -- 0; 6; Embryology, Human.;Abnormalities, Human.;Embryology.;Embryology.;Birth defects; 20; 2